HNP LUMBALIS - Mega Yulia Rusmayanti; Shahdevi Nandar Kurniawan (PERDOSSI (Perhimpunan Dokter Spesialis Saraf Indonesia Cabang Malang) - Indonesian Neurological Association Branch of Malang cooperated with Neurology Residency Program, Faculty of Medicine Brawijaya University, Malang, Indonesia, 2023)
Lumbar herniated nucleus pulposus (HNP) is a disorder characterized by local displacement of the disc beyond the anatomical boundaries of the intervertebral space causing pain, weakness or numbness, and/or tingling in myotomal or dermatomal distribution. HNP is the most common cause of low back pain. Lumbar HNP itself has several underlying etiologies, such as old age, excessive axial load, connective tissue disorders, and congenital abnormalities. Management of HNP can be carried out non-operatively or operatively, depending on the severity, the symptoms that arise, and the response to non-operative treatment.